The relationship between dentistry and forensic medicine (Annals of Medical Research, 2021)
Aim: The study aimed to have an idea about which subjects the relationship between dentistry and forensic medicine focuses on.Material and Methods: In the study, the consultation forms of the patients who were referred from Tokat Gaziosmanpaşa University, Medical Faculty, Forensic Medicine Department to Tokat Gaziosmanpaşa University, Faculty of Dentistry, Oral and Maxillofacial Surgery Department were examined. The forms of the patients admitted between January 2014, and January 2019 were analyzed. Demographic information such as gender, age, and the reasons for consultation was obtained from these forms.Results: In this retrospective study, the consultation forms of sixty-three patients were examined. The reasons for consultation of patients were determined as age estimation (n=32, 50.8%), trauma (n=30, 47.6%) and malpractice (n=1, 1.6%). In patients who were exposed to trauma, physical assault (n=17, 56.7%), traffic accident (n=5, 16.7%), falling (n=2, 6.7%), and firearm injuries (n=1, 3.3%) were among causes of trauma. In the trauma cases, the hard tissues affected in the maxillofacial region were teeth (n=14, 46.7%), symphysis mandible (n=3, 10%), mandibular condyle (n=2, 6.6%) and angulus mandible (n=2, 6.6%). The gender distribution of the patients with age estimation is examined; it is seen that the great majority of them were women (n=30, 93.75%). Furthermore, it is seen that age determination is mostly needed between 15-20 years of age (n=27, 84.4%).Conclusion: A dentist can be appointed as an expert for forensic events in professional life. Therefore, the dentist should pay attention to the training on judicial examination and approach to forensic cases.
Keywords: Dentistry; forensic dentistry; trauma